Character Education Through the Constructivist Design of Islamic Education Subject at Elementary School Pembangunan Jaya II in Gedangan Sidoarjo - Rusydiyah, Evi Fatimatur (AT-TALIM, 2014)
The objective of this study are (1) to determine  the meaning of character education in the elementary school of Pembangunan Jaya II of Gedangan Sidoarjo, (2) to identify how the planning of character education through  constructivist  design on the Islamic  education subjects in the elementary school  of  Pembangunan Jaya II of Gedangan Sidoarjo.  Observation, in-depth interviews and documentation analysis were used in this study. The finding showed that:  (1) elementary school Pembangunan Jaya II in Gedangan Sidoarjo has developed character education. The character education that is developed is  fond of learning character, creative character, independent character and noble, (2) constructivist design that is developed by SD Pembangunan   Jaya II Gedangan Sidoarjo has a component in accordance with the constructivist theory, namely, engage, explore, explain, extend, and evaluate. By the application of habituation based on the constructivist design make the students to have the attitude of eager to learn, creative, independent, and noble character in accordance with the main purpose of the school. Copyright © 2014 by Al-Talim All right reserved